PENINGKATAN KAPASITAS PERSIMPANGAN DENGAN ALAT PEMBERI ISYARAT LALU LINTAS (Studi Kasus : Persimpangan Jl. PB. Sudirman/Raya Puputan/Dewi Sartika Kota Denpasar) - Widana Negara, I Nyoman (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 18, No. 1, Januari 2014, 2016)
At grade intersection connected among Jl.Sudirman S-Jl.Puputan-Jl. Dewi Sartika were controlled by traffic light with 3 stages and with cycle time of 90 seconds. Despite the implementation of one way traffic management, the intersection remains stalled. The purpose of this study is to investigate the capacity management and traffic signal technologies alternatives. The intersection geometry is obtained from topographical surveys while traffic movements are surveyed with a video camera survey. In addition, road side frictions are obtained from the manual traffic counting. The experimental design applied observational techniques and cross section approaches. Three treatments were tested using Indonesia Road Capacity Manual (MKJI). The analysis found that intersection redesigned was reduced the total lost time (LTI) of 22 seconds to 15 seconds (23%), while simulation analysis with MKJI (1997) showed that treatment-3 gave better results compared with treatment-2 and treatment-1. A level of service F (worst) is reached if the intersection is redesigned with a single program control device (treatment-2),
Keywords: junction, capacity, traffic light, Denpasar, Bali